CLINICO-BIOCHEMICAL PROFILE OF HYPOTHYROIDISM IN RHEUMATOID ARTHRITIS - KHAN, PREEMA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The incidence of co-occurrence of multiple autoimmune diseases in a single patient is constantly increasing. Conditions with auto immune backgrounds such as rheumatoid arthritis and thyroid dysfunction have an immense relationship. This study was designed to evaluate the association biochemical parameters and disease progression in rheumatoid arthritis cases with hypothyroidism. Methods: A total of 120 adult participants diagnosed with rheumatoid arthritis with suggestive hypothyroidism between 21 and 55 years of age were included in this study. All cases underwent complete laboratory investigations including thyroid profile. Depending on the diagnostic outcome of the thyroid profile, the participants were divided into two groups, that is, group 1 consists of rheumatoid arthritis with hypothyroidism and group 2 consists of rheumatoid arthritis without hypothyroidism. Results: The higher mean values of FT3 and FT4 were observed in RA with hypothyroidism and mean levels of thyroid function test were statistically significant in between the study groups (p < 0.05). The hypertriglyceridemia in 43.3% cases, hypercholesterolemia in 58.3%, hyperuricemia in 26.6%, and diabetes mellitus in 35% cases were commonly observed metabolic complications. Conclusion: The higher levels of metabolic complications, namely, hypercholesterolemia, hyperuricemia, hypertriglyceridemia, and diabetes mellitus were noticed in rheumatoid arthritis with hypothyroidism. Regular screening of patients is recommended to monitor the status of the condition and to maintain a healthy lifestyle.